Mechanisms of lymphocyte apoptosis at tick-borne encephalitis - O. Ye. Chechina; N. V. Ryazantseva; Ye. V. Sazonova; N. G. Zhukova; I. N. Udintseva; V. V. Novitsky (Бюллетень сибирской медицины, 2011)
Results of the complex research of apoptosis realization of lymphocytes at acute tick-born encephalitis and during long antigenemia condition has been presented in this article. The acceleration of apoptosis, tumor necrosis factor I presentation and the decrease in mitochondrial transmembrane potential of lymphocytes were determined at tick-born encephalitis. Uncovered changes are more appeared at acute neuroinfection.